2009
DOI: 10.1021/ma902206u
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Characterization of Bridged Bithiophene-Based Conjugated Polymers for Photovoltaic Applications: Acceptor Strength and Ternary Blends

Abstract: Six of three-component donor-acceptor random copolymers P1-P6, symbolized as (thiophene donor) m -(thiophene acceptor) n , were rationally designed and successfully synthesized by the palladium-catalyzed Stille coupling. The 4H-cyclopenta[2,1-b:3,4-b 0 ]dithiophene (CPDT) unit serves as the donor for P1-P4, while the benzothiadiazole (BT), quinoxaline (QU), dithienoquinoxaline, and thienopyrazine (TP) units are used as the acceptor for P1, P2, P3, and P4, respectively. P5 and P6 are structurally analogous to P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
124
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 191 publications
(130 citation statements)
references
References 58 publications
4
124
1
Order By: Relevance
“…Contrary to BSe incorporated P2, benzothiadiazole inserted P1 exhibited lower monomer and polymer oxidation potentials due to strong donoracceptor match between pyrrole and BTd units. [26] On the other side, both P1 and P2 have lower oxidation potentials due to the participation of the electron rich pyrrole units to the conjugation. Hence, during the n-type doping of these polymers, higher negative peak potentials for the formation of polymer radical-anions were required which were behind the ACN/TBAPF 6 potential window.…”
Section: Electropolymerizationmentioning
confidence: 99%
“…Contrary to BSe incorporated P2, benzothiadiazole inserted P1 exhibited lower monomer and polymer oxidation potentials due to strong donoracceptor match between pyrrole and BTd units. [26] On the other side, both P1 and P2 have lower oxidation potentials due to the participation of the electron rich pyrrole units to the conjugation. Hence, during the n-type doping of these polymers, higher negative peak potentials for the formation of polymer radical-anions were required which were behind the ACN/TBAPF 6 potential window.…”
Section: Electropolymerizationmentioning
confidence: 99%
“…These results are similar to those of Chen et al, where at lowest optical bandgap low PCE was observed and high PCE was observed at high bandgap. 47 The polymer modified with the nitrogen plasma showed more red-shift, a broader absorption spectrum, high mobility, high bandgap and a higher PCE of 5.14%. In view of this fact, the polymer modified with the nitrogen plasma showed a higher bandgap with intense absorption in the visible region.…”
Section: Characterization Of Bulk Modification Of Polymer Using C-fibmentioning
confidence: 93%
“…The precursors 2,6-dibromo-4,4-diethylhexylcyclopenta[2,1-b:3,4-b 0 ]dithiophene (2) and alkyl 2,5-dibromo thiophene 3-carboxylates (5) were prepared as per reported in the literature [34,35]. Characterization 1 H NMR spectra were recorded on a Bruker 500 MHz spectrometer using deuterated solvents with tetramethylsilane (TMS) as a reference.…”
Section: Experimental Partmentioning
confidence: 99%